Meta-Analysis the Effect of Protected Well and Measles Vaccination on Stunting in Children Under Five - Edi Pramono; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, 2024)
Background: Stunting is a condition where children's growth fails (body and brain growth) due to malnutrition for a long time. The incidence of stunting in toddlers needs special attention because it can hinder children's physical and mental development. This study aims to analyze and estimate the effect of protected wells and the measles vaccine on the incidence of stunting in children under five, with a meta-analysis based on primary studies conducted previously.Subjects and Method: Meta-analysis was carried out in PICO format. Population: Children under five. Intervention: Protected Wells and Measles vaccine status. Comparison: Unprotected Well and Status not vaccinated against measles. Outcome: Stunting incidence. Article searches were carried out using several databases such as Google Scholar, PubMed, Science Direct, and Springerlink. The keywords used are